MAHASISWA SEBAGAI KEKUATAN POLITIK DI ERA DIGITAL - Al-Ra’zie, Zakaria Habib; Apriyanto, Apriyanto (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The digital era brings great changes to society, including in the social and political life of a country. The political dynamics that occur in the digital space can be more dynamic and harsh than in the conventional space. This is due to the ease of public access to voice their opinions on political issues and policies taken by awa government. This shows that the limitations of conventional political space do not apply in the digital political space. One of the political actors who has a big role in the digital space is students. As agents of change , students are morally and intellectually responsible to ensure that the country is on the right path for the benefit of the general public. Among the ways they are through active contributions in voicing opinions using digital instruments that are very mastered, namely social media. In this regard, the researcher is interested in researching the political dimension of students in the digital era. More specifically, this research was conducted to understand what the role of students as political forces in the digital era looks like. This research uses a qualitative method. The data collection technique is carried out through literature study and the data analysis technique used is descriptive analytical. The results of this study found that, in the digital era, students use their political power to mobilize action through various creative ways through social media that are very familiar to their daily lives. The role of students in this context cannot be underestimated, because the impact can be more significant than traditional movements. This is because the digital space is able to keep issues relevant and expand their reach as long as people are connected to the internet, and this creates political movements that are in line with the spirit of the times.Keywords: Students; Political Forces; Digital.